A Power Theory of Third Party Intervention in Labour Management Relations - Hameed, Syed; Sen, Joya (Relations industrielles / Industrial Relations, 1987)
The authors present theoretical constructs of power and theoretical concepts as they apply to motivation, conflict and negotiation.